Grammatical Error Analysis Of Written English Compositions Produced By First Grade Of Islamic Banking Student Of Stain Syaikh Abdurrahman Siddik Bangka Belitung In Academic Year 2017 - M Afifulloh (STAIN Bengkalis, 2018)
This final project primarily deals with grammatical error analysis of 26 English compositions written by first grade Islamic Banking student of Islamic State Collage (STAIN) Syaikh Abdurrahman Siddik Bangka Belitung in academic year 2017. The instrument used for this study was participants’ written composition in English language. All of the errors in these compositions were identified and classified into different categorizations. The results show that the students in this study committed fifteen errors. These errors are S-V agreement (17%), capitalization (15%), article (9.1%), punctuation (7.7%), omission/addition of to be (6.2%), word choice (5.1%), gerund/infinitive (7%), plurality (5.1%), verb tense (11.7%), modal (2.5%), pronoun (3.3%), preposition (4.4%), negative (3.3%), and sentence fragment (7.2%). There is the hope that the paper helps English teachers to become familiar with the most frequent errors committed by students and to adopt appropriate teaching strategies to help the learners learn better.